A Validation of a Reading Comprehension Test for University Students - Brizuela Rodríguez, Armel (2019)
The goal of this article is to provide evidence as to the validity and reliability of a new Reading Comprehension test aimed at college students which is based on an observational and cross-cutting research design. The test was taken by 244 students in the first year of their major. The results were analyzed according to the Classical Test Theory, the Rasch Model and a Pearson correlation coefficient to compare the scores obtained with first year courses taken by students for their Major. As a result of the study, a 44-item was elaborated with a reliability scale of 0.74 and a statistically significant correlation scores of 0.21 [0.09, 0.33] (p < 0.000) for student grades in first-year courses. It can be concluded that this test could be useful to detect reading comprehension difficulties among first-year university students which could potentially negatively impact their academic performance. The test could also serve as a screening tool in the development of remedial programs to strengthen reading comprehension among these students.